Effect of gas cooking on lung function in adolescents: modifying role of sex and immunoglobulin E. Issue 7 (1st July 2001) - Corbo, G M; Forastiere, F; Agabiti, N; Dell'Orco, V; Pistelli, R; Aebischer, M L; Valente, S; Perucci, C A
Abstract : BACKGROUND: A study was undertaken to investigate the effect of gas cooking on the lung function of adolescents while considering serum IgE level as a possible effect modifier. METHOD: The cross sectional study was performed in 702 subjects aged 11–13 years from primary and secondary schools in Civitavecchia and Viterbo ( Latium region in Central Italy), categorised according to how often they were in the kitchen while the mother cooked (never, sometimes, often). Data were collected by questionnaire and lung function was measured by spirometric tests. Bronchial hyperresponsiveness was evaluated by the methacholine test, atopic status by a skin prick test, and a blood sample was collected to determine serum IgE levels. The results were analysed separately for boys and girls. Multiple regression analysis was performed, taking functional parameters (FEV1, FEV1 /FVC, FEF25–75, FEF50, FEF75 ) as the dependent variables and age, height, parental smoking, and father's education as independent variables. RESULTS: There was no association between time spent in the kitchen and lung function level in boys, but a reduction in lung function was detected in girls which was statistically significant for FEF75 (sometimes –10.3%, often –11.1%). After stratifying boys and girls into four groups on the basis of the IgE serum level (below and above the median value of IgE), the reduction in lung function was significant in girls with a high IgE value whereas no significant deleterious effects were evident in girls with a low IgE value or in boys with either a low or high IgE. The results remained substantially unchanged after excluding girls with a response to methacholine below the concentration of 4 mg/ml, asthmatic patients, and those with positive skin prick tests. CONCLUSION: Gas cooking has a harmful effect on the lung function of girls with a high serum level of IgE. We do not know whether serum IgE, a marker of allergic susceptibility, is a simple indicator that an inflammatory process is in progress or whether it is involved in the pathogenesis of injury leading to bronchial obstruction.